SYNTHESES AND CYTOTOXICITY ASSAY OF ANALOGUES OF UK-3A, A NOVEL FROM Streptomyces sp. 517-02 - Anita, Yulia; Hanafi, M.; Arifin, S. (Teknologi Indonesia, 2013)
UK-3A is a minor compound from the mycelium of Streptomyces sp.517-02 and had been isolated. It has IC50 38 ?g/mL against P388 Murine Leukemia cells. Products of UK-3A analogues were assigned the name A and B compounds. These compounds were prepared from L-serine methyl ester-HCl as starting material and synthesized by amidation and esterifi cation. The products were determined by TLC, FT-IR, MS and NMR instruments. Theoverall yield was compounds A 95.63% and B 87.10%. The in vitro anticancer activities of compounds A and B against the same Leukemia cells and found to have IC50 46.5?g/mL and 15.4?g/mL, respectively. The compound B exhibited higher inhibitory activity than UK-3A.